Vous êtes sur la page 1sur 5

f a a

I a

b ∈ I − {a } f a b

f (b )

f (a ) b a

f I

x

h > 0 x + h ∈ I f x x + h

f (x + h) f (x )

h

f a b

(a ; f (a )) (b ; f (b ))

1. 0
B
1. 24
0. 5
A
− 0. 5
0. 5
1. 0
1. 5
− 0. 5

y = y B y A x = x B x A

y = y B

x

y A = f (b )

f (a ) b a

x B x A

d d

1. 0
B
0. 5
∆ y
A
∆ x
− 0. 5
0. 5
1. 0
1. 5
− 0. 5

x t t x (t )

t 1 t 2

x = x (t 2 ) x (t 1 )

t

t 2 t 1

x = x (t 1 + ∆ t ) x (t 1 )

t

t

f I x

f x

f (x ) = lim

h

0

f (x + h) f (x )

h

x

1. 0
0. 5
0. 7
A
0.
5
0. 5
1. 0
1. 5
0. 5

A 0, 7

f I x

f x f (x ) φ

h > 0 x + h ∈ I

f (x + h) = f (x ) + hf (x ) + (h) lim h 0 φ(h) = 0

1.
0
0.
5
A
0. 5
0. 5
1. 0
1. 5
0. 5

t

x (t )

(t 1 ) dt

dx

= lim

t0

x (t 1 + ∆ t ) x (t 1 )

t

x (t 1 )

f x y f (x )

dy

dx

= f (x ) dy = f (x )dx

f I

f f x ∈ I

f x f (x )

f (x )
f (x )
0
R
C
x
1
R
x 2
2x
R
1
R ∗
x
− x 1
2
nx n − 1
x n n ∈ N
R
1
− n
R ∗
x n
x n +1
x
1
R +
sin(x )
2 √ x
cos(x
)
R
cos(x
)
− sin(x )
R
tan(x
)
1 (x ) 1 + tan 2 (x )
R − { π + kπ, k ∈ Z }
2
cos 2

f g I

 (f + g ) = f + g (− f ) = − f (fg ) = f g + fg

f = f g

g

g

2

fg

g I

( f n ) = nf n 1 n

f =

f

2 f f I

f I I

f I a ∈ I f a

f a

f (a + h) = f (a ) + hf (a ) + (h) lim h 0 φ(h) = 0

x = a + h

f (x ) = f (a ) + (x a )f (a ) + (x a )φ(x a )

f (a )

lim x a (x a )f (a ) = 0

lim x a (x a )φ(x a ) = 0

lim a f (x ) = f (a )

x

f a

f

: x x sin 1

x 0

0 0

f (x ) f (0)

x

=

x sin

x

1

x

= sin

x

1

x 0 f 0

u v v J u

I u ( I ) ⊂ J

v u v u x v u(x ) = v (u(x )) I

x ∈ I

( v u(x )) = u (x ) × v (u(x ))

dv (u) = du × dv (u)

dx

dx

du